Minimum-Norm Estimation of TMS-Activated Motor Cortical Sites in Realistic Head and Brain Geometry - Jusa Reijonen; Laura Saisanen; Minna Pitkanen; Meri Julkunen; Risto J. Ilmoniemi; Petteri Nieminen; Petro Julkunen (IEEE, 2022)
Navigated transcranial magnetic stimulation (nTMS) is a widely used tool for motor cortex mapping. However, the full details of the activated cortical area during the mapping remain unknown due to the spread of the stimulating electric field (E-field). Computational tools, which combine the E-field with physiological responses, have potential for revealing the activated source area. We applied the minimum-norm estimate (MNE) method in a realistic head geometry to estimate the activated cortical area in nTMS motor mappings of the leg and hand muscles. We calculated the MNE also in a spherical head geometry to assess the effect of the head model on the MNE maps. Finally, we determined optimized coil placements based on the MNE map maxima and compared these placements with the initial hotspot placement. The MNE maps generally agreed well with the original motor maps: in the realistic head geometry, the distance from the MNE map maximum to the motor map center of gravity (CoG) was 8.8 ± 4.6 mm in the leg motor area and 6.6 ± 2.5 mm in the hand motor area. The head model did not have a significant effect on these distances; however, it had a significant effect on the distance between the MNE CoG and the motor map ( ${p} < 0.05$ ). The optimized coil locations were < 1 cm from the initial hotspot in 7/10 subjects. Further research is required to determine the level of anatomical detail and the optimal mapping parameters required for robust and accurate localization.